RESPON KETAHANAN BERBAGAI VARIETAS TOMAT TERHADAP PENYAKIT LAYU BAKTERI (Ralstonia solanacearum) - Adriani, Adriani; Rahman, Abdul; Gusnawaty, HS; Khaeruni, Andi (Jurnal Agroteknos, 2012)
The study was aimed to know the resistance response of some tomato varities to bacterial wilt disease (Ralstonia solanacearum). The study was arranged in a completely randomized design (CRD) with six tomato variety treatmens, namely : Permata, Cosmonot, Idola, Gress, Ratna, and a local Muna variety. Each treatment had three replicates of six plants. The resistance response observed were : the latent period, disease incidence, disease severity, and plant height. The response was observed weekly until 7 weeks after inoculation. The results showed that Cosmonot variety was resistant to bacterial wilt disease, without any disease incedence occured and the disease severity was only 6,66%. Whereas the Local Muna variety as well as Permata, Gress, and Idola were susceptible to bacterial wilt disease. On the other hand, Ratna variety showed slight tolerant response. Keywords : bacterial wilt, Ralstonia solanacearum, resistance reaction, tomato variety